Synthesis, crystal structure, bioactivities of Ni(II), Cu(II), Co(II) and Pd(II) complexes with unsymmetrical thioether donor Schiff base: Phosphine free Pd(II) complex catalyzed Suzuki reaction. (5th September 2015) - Kalita, Mukul; Tamuli, Kashyap Jyoti; Barman, Pranjit; Sarma, Bipul; Baruah, Reshita; Deka Boruah, Hari Prasanna
Graphical abstract: A series of new Ni(II), Cu(II), Co(II) and Pd(II) complexes were synthesized from the reaction of thioether containing Schiff base ligand with corresponding metal salts by a simple environmentally benign procedure. Copper forms square planar geometry. As expected, nickel complex acquired a distorted octahedral geometry. The reported palladium complex is phosphine free, air stable, moisture insensitive. Ligand and complexes show very good activity against Mycobacterium abscessus, Bacillus subtilis, Staphylococcus aureus, Proteus vulgaris, Mycobacterium smegmatis and Escherichia coli . Abstract: A series of new Ni(II), Cu(II), Co(II) and Pd(II) complexes were synthesized from the reaction of thioether containing Schiff base ligand with corresponding metal salts by a simple environmentally benign procedure. The molecular formulae of ligand and their complexes are (C21 H19 NO2 S)2, 1, [Ni(C21 H18 NO2 S)2 ]·CH3 OH·H2 O, 2, [M(C21 H18 NO2 S)2 ] (3 and 4), where (M = Cu(II) and Co(II)) and [Pd(C21 H18 NO2 SCl)](5). All complexes were characterized by elemental analysis, FT-IR, UV–Vis spectroscopy and single crystal X-ray diffraction analysis. The ligand was characterized by same techniques and with 1 H NMR spectroscopy. X-ray diffraction study reveals that copper complex adopts square planar geometry by coordinating via deprotonated hydroxyl oxygen, azomethine nitrogen of ligand to the copper centre and sulfur atoms remain unligated. As expected, nickel complex acquired a distorted octahedral geometry coordinating via deprotonated hydroxyl oxygen, azomethine nitrogen and thioether sulfur atoms of ligands. Interestingly, one water and one methanol molecule are attached at the out sphere of the nickel complex. Suzuki reaction was carried out in open atmospheric conditions using palladium complex as catalyst. The significant features of the palladium complex catalyzed reaction are good yield, simple workup procedure, easy purification and easy recovery technique of the catalyst. The reported palladium complex is phosphine free, air stable, moisture insensitive. The ligand and complexes show very good biological activities against Mycobacterium abscessus, Bacillus subtilis, Staphylococcus aureus, Proteus vulgaris, Mycobacterium smegmatis and Escherichia coli .